2006
DOI: 10.1038/ncb1500
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of colonic homeostasis by distinctive apical TLR9 signalling in intestinal epithelial cells

Abstract: The mechanisms by which commensal bacteria suppress inflammatory signalling in the gut are still unclear. Here, we present a cellular mechanism whereby the polarity of intestinal epithelial cells (IECs) has a major role in colonic homeostasis. TLR9 activation through apical and basolateral surface domains have distinct transcriptional responses, evident by NF-kappaB activation and cDNA microarray analysis. Whereas basolateral TLR9 signals IkappaBalpha degradation and activation of the NF-kappaB pathway, apical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
505
2
13

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(544 citation statements)
references
References 45 publications
24
505
2
13
Order By: Relevance
“…Recently, TLR9 has been proposed to play a key role in the regulation of intestinal immunity. TLR9 blocks signalling via other TLRs and provides protection against intestinal colitis by stimulation of the production of IFNs (Katakura et al, 2005;Lee et al, 2006). In mIC cl2 cells, we did not detect TLR9 mRNA under steady-state conditions, but rather found TLR5 as a key regulatory molecule.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Recently, TLR9 has been proposed to play a key role in the regulation of intestinal immunity. TLR9 blocks signalling via other TLRs and provides protection against intestinal colitis by stimulation of the production of IFNs (Katakura et al, 2005;Lee et al, 2006). In mIC cl2 cells, we did not detect TLR9 mRNA under steady-state conditions, but rather found TLR5 as a key regulatory molecule.…”
Section: Discussioncontrasting
confidence: 64%
“…Real-time RT-PCR demonstrated that mIC cl2 cells also express TLR2 and TLR5 (Table 1). Unlike Caco-2 cells (Lee et al, 2006), mIC cl2 cells do not express TLR9 (not shown). Expression of TLR4 and TLR5 mRNA in mIC cl2 cells is comparable to BMDCs and C3H/HeJmTLR4 macrophages, whereas expression of TLR2 mRNA is 10-fold lower ( Table 2).…”
Section: Functional Analysis Of Tlr2 Tlr4 and Tlr5 In Mic Cl2 Cellsmentioning
confidence: 92%
“…Cellular activation is reported to induce TLR9 expression in additional cell types, including human neutrophils (Hayashi et al, 2003), monocytes and monocyte-derived cells (Saikh et al, 2004;Siren et al, 2005) and CD4 T cells (Gelman et al, 2006), but the biologic role for this is less well understood. TLR9 expression has also been reported in some nonimmune cells, including pulmonary epithelial cells and lung cancers (Li et al, 2004;Platz et al, 2004;Droemann et al, 2005), keratinocytes (Lebre et al, 2007) and intestinal epithelium (Pedersen et al, 2005;Lee et al, 2006). TLR9 recognizes and is activated by unmethylated cytosine-phosphate-guanine (CpG) dinucleotides, which are relatively common in bacterial and viral DNA but are suppressed and methylated in vertebrate DNA (Krieg, 2004).…”
Section: Toll-like Receptormentioning
confidence: 99%
“…Examples of such sentinel elements are Toll-like receptors (TLRs) and related Nod-like receptors (NLRs), collectively termed "pattern recognition receptors" (PRRs), that bind to motifs known as "microbe associated molecular patterns" (MAMPs) that are ubiquitously present across the bacterial phylogenetic domain [24]. Sensing of MAMPs by TLRs activate innate immune signaling cascades such as the MAPK and NF-kB pathways [25][26][27][28], which are by and large considered pro-inflammatory, although at lower 'tonic' levels of activation, have been connected to mechanisms of normal gut homeostasis [29,30].…”
Section: Epithelial Perception and Monitoring Of The Microbiotamentioning
confidence: 99%